1997
DOI: 10.1523/jneurosci.17-23-08975.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin Dependent Kinase Inhibitors and Dominant Negative Cyclin Dependent Kinase 4 and 6 Promote Survival of NGF-Deprived Sympathetic Neurons

Abstract: Neuronal apoptosis plays a critical role in both normal development and disease. However, the precise molecular events controlling neuronal apoptosis are not well understood. Previously, we hypothesized that cell cycle regulatory molecules function in controlling the apoptotic pathways of trophic factor-deprived neurons. To test this hypothesis, we used the RNA alphavirus Sindbis to express three known cyclin dependent kinase inhibitors (CKIs), p16(ink4), p21(waf/cip), and p27(kip1), and dominant negative muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
198
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(220 citation statements)
references
References 52 publications
21
198
1
Order By: Relevance
“…One of the early observations in this field was the finding that the withdrawal of nerve growth factor (NGF) from sympathetic neurons induces the expression of cyclin D1 expression in these neurons (Freeman et al, 1994). This observation was extended to a number of paradigms of neuronal apoptosis, including activity deprivation of cerebellar granule neurons and the exposure of neurons to DNA-damaging agents and other pathogenic stimuli (Park et al, 1997(Park et al, , 1998Padmanabhan et al, 1999). In these studies, the induction of cyclin D1 was found to lead to the activation of D1-associated cdk4/6, and inhibition of these kinases protected neurons against apoptosis (Park et al, 1997(Park et al, , 1998Padmanabhan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…One of the early observations in this field was the finding that the withdrawal of nerve growth factor (NGF) from sympathetic neurons induces the expression of cyclin D1 expression in these neurons (Freeman et al, 1994). This observation was extended to a number of paradigms of neuronal apoptosis, including activity deprivation of cerebellar granule neurons and the exposure of neurons to DNA-damaging agents and other pathogenic stimuli (Park et al, 1997(Park et al, , 1998Padmanabhan et al, 1999). In these studies, the induction of cyclin D1 was found to lead to the activation of D1-associated cdk4/6, and inhibition of these kinases protected neurons against apoptosis (Park et al, 1997(Park et al, , 1998Padmanabhan et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that abortive reentry into the cell cycle by activation of cell cycle components is responsible for apoptosis in granule neurons and other neuronal types (Park et al 1997a(Park et al , 1997bPadmanabhan et al 1999). It was thus possible that the neuroprotective effect of GW5074 was mediated by cdk inhibition.…”
Section: Gw5074 Inhibits Lk-induced Apoptosis In Cerebellar Granule Nmentioning
confidence: 99%
“…(16) Pharmacologic and genetic inhibitors of cyclindependent kinases can effectively block neuronal apoptosis, further suggesting that cell-cycle activity is not simply an epiphenomenon of neurodegeneration. (10,11,17,18) Whereas a cycling cell is competent to proceed through mitosis and thereby couple DNA repair with cell division, a post-mitotic neuron inherently lacks certain proteins critical for nuclear division (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, withdrawal of NGF from cultured PC12 (pheochromocytoma) cells induces pro-apoptotic cyclin-associated activities that are blocked by CDK inhibitors such as flavopiridol and dominant negative forms of CDK4 and CDK6. (10,17) Kainate-mediated excitotoxicity in primary cerebellar granule cells is associated with upregulation of cyclin D1 (11) and of cyclin E, CDK2 and E2F-1 (12) and is attenuated by inhibitors of CDKs and mitogen-activated proteins. (11) Administration of ceramide has been shown to induce nuclear translocation of NF-kB and activation of cyclin D1 in a primary neuronal system, events that precede caspase activation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%